IN THE WORK OF ALISHER NAVOI IDEAS OF EDUCATION AND HUMANITY - Saparnyozova Diyora Shodurdiyevna (TADQIQOTLAR.UZ, 2023)
Comment: "The article contains articles about universal human qualities, manners, education in the work of Alisher Navoi, the sultan of the word property, the place of the spiritual treasure of the artist in children's literature, his contribution to the development of schools and madrasas and ". (darris) direct image is described.